1997
DOI: 10.1177/074193259701800202
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Teachers' Instructional Interactions with Students Who Are Exceptional, At Risk, and Typically Achieving

Abstract: The conversational interactions of 9 teachers and their third-grade students were recorded during individual seatwork time in academic lessons. teachers' views about their responsibilities in working with students who are exceptional or at risk of academic failure were quite divergent and were related to their instructional discourse strategies. teachers who saw themselves as instrumental in effective inclusion engaged in more academic compared to nonacademic interactions. this group also exhibited greater use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 19 publications
1
59
0
1
Order By: Relevance
“…This might suggest that some teachers are more inclined to use those attributions as explanations for student failure than other teachers. These results could support, or be supported by, studies that examined the differing perspectives that teachers hold about their responsibilities in dealing with low achieving students, the effect on the attributions they use and behaviour they show (Jordan and Kircaali-Iftar 1993;Jordan et al 1997). In these studies it has been concluded that some teachers are more likely to attribute failure to student ability and/or their families, than other teachers.…”
Section: Disussions and Implications For Research On Attributionsmentioning
confidence: 61%
See 2 more Smart Citations
“…This might suggest that some teachers are more inclined to use those attributions as explanations for student failure than other teachers. These results could support, or be supported by, studies that examined the differing perspectives that teachers hold about their responsibilities in dealing with low achieving students, the effect on the attributions they use and behaviour they show (Jordan and Kircaali-Iftar 1993;Jordan et al 1997). In these studies it has been concluded that some teachers are more likely to attribute failure to student ability and/or their families, than other teachers.…”
Section: Disussions and Implications For Research On Attributionsmentioning
confidence: 61%
“…In light of providing each student with an optimal learning environment it seems important that teachers are aware of the attributions they make for individual students and the consequences of these attributions for their student-directed behaviour. Teacher awareness of the learning needs of individual students is important (Tomlinson et al 2003;Jordan et al 1997), especially within the current educational climate of inclusion and the accompanying demand on teachers to address all individual students' learning needs (Ferguson 2008). This is even more important with regard to the needs of low achieving students who are struggling in class and who are most in need of adequate adaptation of student-directed teacher behaviour.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These teachers try significant interventions prior to making referrals to special education, work with support personnel using a team-based approach, link assessment procedures with their curriculum and instructional methods, and have regular communication with parents. Interventionist teachers are accepting of the increasing classroom diversity resulting from changes in sociocultural conditions and educational policy, and they engage in more academic interactions with their students and are more persistent in actively assisting students to construct understanding (Jordan, Lindsay, & Stanovich, 1997). The P-I Questionnaire, developed from the P/I Interview for the present study, yields a mean score of teachers' ratings of their beliefs about their roles and their practices in working with integrated exceptional and at-risk students.…”
Section: Procedures and Methodsmentioning
confidence: 99%
“…Quality of instructional interactions. A classroom observation system was designed for the present study based on earlier work conducted by Jordan et al (1997). In that study the quality of instructional interaction was described in terms of three levels:…”
Section: Procedures and Methodsmentioning
confidence: 99%